PENERAPAN PENYELESAIAN MASALAH HELLER UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL MATERI GERAK LURUS - Karisma Lestari; Haratua Tiur Maria S; Diah Mahmudah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to show the effectiveness of the implementation of the Heller’s problem solving in improving student’s ability to solve questions on straight-motion at SMAN 6 Pontianak. One group pretest-posttest was used in this study. This study involved 27 students of grade XI which had taken by intact group. The instruments of this study were 5 essays pretest and posttest. Based on pretest’s data analyze, visualize the problem was the highest student’s ability (49,8%) and execute the plan was the lowest student’s ability (20%).But according to posttest’s data analyze, visualize the problem was the most mastered by students (90,8%). The improvement of problem-solving ability was calculated by gain-score test, and got 0,33 in fairly good category. Heller’s problem solving was effective in improving student’s ability to solve the questions with the effect size of 1,4 in the high category. So, this study could be an alternative in improving student’s ability to solve the questions. Keywords: Ability, Straight-motion, The Heller’s Problem Solving